Perbandingan Efektivitas Bioadsorben Berbagai Serbuk Kulit Buah Terhadap Logam Pb Dari Limbah Cair Laboratorium Farmasi - Hesty Nuur Hanifah; Ginayanti Hadisoebroto (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2021)
Pharmaceutical laboratory liquid waste is a source of heavy metal contaminants that can be harmful to living things if not treated properly. One of these heavy metals is lead (Pb), which if accumulated in the body can cause kidney disorders, nerves and even death. Utilization of bioadsorbents derived from biomass in the form of fruit peels can be a solution because they generally contain compounds that have functional groups that can bind to metals. The purpose of this study was to reduce Pb levels in liquid waste using a biomass waste adsorbent made from five) kinds of fruit peel powder, namely jackfruit peel, salak, durian, banana and watermelon.. The adsorption process must be carried out under optimal conditions, by varying the pH factor, immersion time and mass of the bioadsorbent powder. Measurement of Pb levels was carried out using Atomic Absorption Spectrophotometer (AAS) at a wavelength of 283.3 nm. The results showed that the highest adsorption effectiveness was obtained using jackfruit peel powder, which was 94.74%,. While the lowest adsorption effectiveness was using banana peel powder, which was 57.29. The adsorption effectiveness of watermelon, salak and durian peel were 91.52%, 90.5% and 63.74%, respectively.